2022
DOI: 10.3390/idr14040056
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Avian Influenza Subtype H9 Outbreaks in Poultry Farms of Central Lowland Nepal

Abstract: Low pathogenic avian influenza (LPAI) of subtype H9 outbreaks have been frequently occurring in major commercial hubs of Nepal including Chitwan, a central lowland area, causing substantial economic losses to the farmers. However, the risk factors associated with these outbreaks have been poorly understood, and hence, this case-control study was conducted in Chitwan, Nawalpur, and Makawanpur districts of Nepal from October 2019 to March 2020. A total of 102 farms were selected in which 51 were case farms, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
2
1
Order By: Relevance
“…In the present study, no access of visitors into the poultry farms has been reported as a significant protective factor against AIV transmission, whereas the previous studies illustrated that visitors not allowed from other poultry farms and retail markets significantly reduce the odds of AIV transmission ( 80 , 85 ). In our study, we observed that the predicted prevalence of AIV transmission was reported to be only 12% where there were no access visitors to the turkey farms, whereas, in the previous study by Subedi et al ( 86 ), this risk was reported to be 2.8 times higher in commercial farms where visitors are allowed to sheds during the H9 outbreak. Visitors such as veterinarians and technicians visit multiple farms in a day for Newcastle disease (ND) vaccinations without thorough decontamination, contributing significantly to AIV transmission between farms ( 87 ), as ND and AIV frequently co-infect in poultry farms ( 88 ).…”
Section: Discussioncontrasting
confidence: 63%
“…In the present study, no access of visitors into the poultry farms has been reported as a significant protective factor against AIV transmission, whereas the previous studies illustrated that visitors not allowed from other poultry farms and retail markets significantly reduce the odds of AIV transmission ( 80 , 85 ). In our study, we observed that the predicted prevalence of AIV transmission was reported to be only 12% where there were no access visitors to the turkey farms, whereas, in the previous study by Subedi et al ( 86 ), this risk was reported to be 2.8 times higher in commercial farms where visitors are allowed to sheds during the H9 outbreak. Visitors such as veterinarians and technicians visit multiple farms in a day for Newcastle disease (ND) vaccinations without thorough decontamination, contributing significantly to AIV transmission between farms ( 87 ), as ND and AIV frequently co-infect in poultry farms ( 88 ).…”
Section: Discussioncontrasting
confidence: 63%
“…Agriculture contributes 25.83% of the national gross domestic product (GDP), while the livestock sector alone contributes 13% of the GDP and 27% of the agriculture GDP [ 11 ]. In Nepal, poultry farming is rapidly expanding, and the country is self-sufficient in the production of chicken meat and eggs [ 12 ]. Around the Kathmandu Valley, there has been a report of high antibiotic usage, including reserve antibiotics for human medicine [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Viral infections, including avian influenza and Newcastle disease (ND) are the major health problems in the poultry industry of Nepal [1,4,5]. ND is also known as Ranikhet and is caused by Newcastle disease virus (NDV), aka avian paramyxovirus serotype 1, which is a single-stranded RNA virus with non-segmented genome [6].…”
Section: Introductionmentioning
confidence: 99%